Pengaruh Struktur Modal, Ukuran Perusahaan, dan Profitabilitas Terhadap Nilai Perusahaan : Studi Empiris pada Perusahaan Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Febrina Cahyaningtias; Uswatun Khasanah; Triana Yuniati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to test and analyze the influence of capital structure, firm size, and profitability on firm value. This research employs a quantitative research method, with secondary data sourced from the annual financial statements of companies listed on the Indonesia Stock Exchange. The population and sample in this study are companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange during the 2019-2023 period. The sampling technique used is purposive sampling based on specific criteria, resulting in 160 samples. The analysis methods used are descriptive statistical tests, classical assumption tests, panel data regression analysis, and hypothesis testing. The results of this study show that: (1) capital structure does not affect firm value; (2) firm size does not affect firm value; (3) profitability has a positive and significant effect on firm value. These findings provide both theoretical and practical contributions to understanding the factors that influence firm value in the basic industry and chemical sector in Indonesia.